FREEDOM OF INFORMATION IN INDONESIA AND AUSTRALIA - Partridge, Jodie (Faculty of Law, Universitas Brawijaya, 2015)
Freedom of Information laws promote access to data held by government authorities in the public sector to mainstream society. Such laws have been enacted on a global scale however the obedience they have attracted is not consistent amongst each geographical location. Freedom of Information Laws have been enacted in Indonesia, it was a scheme introduced in 2008 which included many different components that were to improve each individual's right to communicate and obtain information for the purpose of developing themselves and their current political and social environment. The adequacy of the Freedom of Information is a questionable notion in the grand scheme of Indonesia's legal environment as its effectiveness and motives are rather questionable. It has been acknowledged that this initiative is still developing on a national scale, which raises the main question, is 6 years long enough for a scheme to still be dubbed as 'developing'? This text will analyse the advantageous and pitfalls of the legislative instrument ending with a comparative analysis with the current situation that Australia experiences.